1993
DOI: 10.1038/365156a0
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of T-cell receptor signalling by tyrosine protein kinase p50csk

Abstract: Tyrosine protein phosphorylation is necessary for antigen receptor-mediated activation of T lymphocytes. This signal is generated at least in part by the Src-related tyrosine protein kinases p56lck and p59fynT (refs 2, 3). The activity of these two enzymes is repressed by phosphorylation of a conserved carboxy-terminal tyrosine residue. Recent studies suggest that this inhibitory phosphorylation may be caused by p50csk (for C-terminal Src kinase), a tyrosine protein kinase which accumulates most abundantly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
219
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(233 citation statements)
references
References 23 publications
12
219
0
Order By: Relevance
“…Fyn has been shown to play an essential role in the platelet-derived growth factor receptor (51), Ig (52), and T-cell receptor (53) signaling. In addition, we have shown that Fyn is activated during PRL stimulation of Nb2 cells (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…Fyn has been shown to play an essential role in the platelet-derived growth factor receptor (51), Ig (52), and T-cell receptor (53) signaling. In addition, we have shown that Fyn is activated during PRL stimulation of Nb2 cells (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to elucidate whether the weak responses to anti-oxidant treatment were related to ongoing apoptotic cell death, we measured the ratio of apoptotic 14 A. Cayota et al cells by flow cytometry [19,20]. Results depicted in Fig.…”
Section: Anti-oxidant Treatment Restored Cd45-associated Phosphatase mentioning
confidence: 99%
“…Rabbit antisera directed against Lck, Fyn, Csk, Chk, Zap-70, Syk, Cbl, Vav, and Shc were described previously (36,(42)(43)(44)(45)(46)(47)(48). Monoclonal antibodies (MAbs) reacting with CD45 (M1.89.18.7), TCR (F23.1 and H57), CD3 (145-2C11 for immunoprecipitation; HMT-3 for immunoblotting), (H146), Thy-1 (G7), CD4 (GK1.5), CD8 (2.43), Tac (7G7), and Myc (9E10) were reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%